UJI STABILITAS FORMULASI KRIM TABIR SURYA SERBUK RUMPUT LAUT (Eucheuma cottonii. Doty) - Hamsinah Hamsinah; Sasanti D. Darijanto; Rachmat Mauluddin (Faculty of Pharmacy, Universitas Muslim Indonesia, 2016)
Over sunlight exposure in long periode may cause skin damage, premature aging, and skin cancer possibilitie. Sunsreen can protect the skin from negative effect of sunlight, it can reduce the negative effect of UV radiation. Seaweed powder Eucheuma cottonii. Doty is one of the sea plants that can be used as a sunscreen. The objective of this research was to evaluate the physical stability of cream seaweed powder (Eucheuma cotonii. Doty). Cream evaluation included organoleptic, pH, viscosity, freeze an thaw, and sentrifuge test. The organoleptic examination that has been done does not change the smell, color, fungal growth, and does not form a layer on the surface of the creams, and creams remain homogeneous. Emulsion type of preparation was the water in oil. The effect of storage time on viscosity creams are not significant changes. The result sentrifuge test at a speed of 3800 rpm for 5 hours showed the cream to remain stable, and there was no phase separation. Cream storage at two different temperatures or freeze thaw cycle was stable there were no phase separation until the cycle to six.